2020
DOI: 10.26623/themessenger.v12i2.2244
|View full text |Cite
|
Sign up to set email alerts
|

(Opportunities) Death of Newspaper Industry in Digital Age and Covid-19 Pandemic

Abstract: <div class="WordSection1"><p><em>Newspaper industry is entering a state of emergency in Indonesia. Dewan Pers demands that the government provide incentives to press companies during Covid-19. The growth in the number of internet users, the downward trend in advertising revenue, and the number of newspaper circulation are problems in the print media business. List of questions in this study: what are the trends in the use of internet technology and social media in Indonesia?; why did various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 4 publications
0
10
0
3
Order By: Relevance
“…The development of information technology has supported innovations to help people do something easier (Burbules et al, 2020;Kintu et al, 2017;Liao et al, 2018). The development of technology increases the number of internet users in which in Indonesia it reaches 17 percent or 25 million with an average usage of 7 hours 59 minutes per day mostly for social media (Fardiah et al, 2020;Supadiyanto, 2020). The number of social media users in Indonesia is 175.4 million people with an average usage of 3 hours 26 minutes per day.…”
Section: Introductionmentioning
confidence: 99%
“…The development of information technology has supported innovations to help people do something easier (Burbules et al, 2020;Kintu et al, 2017;Liao et al, 2018). The development of technology increases the number of internet users in which in Indonesia it reaches 17 percent or 25 million with an average usage of 7 hours 59 minutes per day mostly for social media (Fardiah et al, 2020;Supadiyanto, 2020). The number of social media users in Indonesia is 175.4 million people with an average usage of 3 hours 26 minutes per day.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, it is also important that newspaper media business firms to not focus only on technological factor, but also on maintaining credibility and veracity of their news delivery. A business firm's capability to merge and mix newspaper technologies will determine its success (Supadiyanto, 2020). The development of a business model innovation is not only related to technological management and innovation, but will also be determined by the corporate strategy and the informational system adopted by firms (Winterhalter et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In collateral, the rise in printing costs creates further weight for newspaper business firms. On the other hand, online media as sources for information have blossomed out significantly (Supadiyanto, 2020). Consistent with this, (Jadhav, 2020) also reported that because of Covid-19 Pandemic, newspaper industry in India have been disrupted in their production and distribution of newspapers as well as experiencing reduction in advertisements income.…”
Section: Introductionmentioning
confidence: 89%
“…The global crisis has a wide impact spanning across all industries. As this paper was written, we saw evidence of this from sectors such as manufacturing [ 11 ], exports [ 12 ], media [ 13 ], and construction [ 14 ].…”
Section: Introductionmentioning
confidence: 99%